STUDY OF NIKEL DOPED MOF-5W LUMINESCENT PROPERTIES - Afiffah, Amatullah
Toxic dan harmful gas such as CO and CO2 are colorless and odorless, so they cannot be easily detected by naked eye. It is necessary to develop a gas sensors to detect the presence of these gases, where gas sensors are generally based on semiconductor materials which have a narrow surface and high operating temperatures. Developing gas sensor requires a large surface area material to increase sensitivity and an easy detection mechanism that does not require high temperatures. The candidate material which has a large surface area is metal organic framework. In this research, a photoluminescent properties study was conducted on MOF-5W, a stable phase and fluorescent material. In this study, MOF-5W doping was also carried out using nickel to determine the photoluminescence properties and the band gap value due to doping. The FTIR and P-XRD characterization were carried out to see the structure, as well as DRS-UV and spectrofluorescence to see the optical properties of the synthetic material. The results obtained are that MOF-5W and Ni-MOF-5W have similar direct band gap values (3.74 and 3.69 eV) but have quite different indirect band gap values (3.4 and 3.25 eV). Photoluminescent properties studies show that MOF-5W and Ni-MOF-5W have similar excitation and emission peaks (excitation = 282 nm, emission 430 nm). Doping makes the material emission intensity decreased.